The WLIC/IFLA Conference in Buenos Aires 2004 - Denise, Nicholson (Library and Information Association of South Africa (LIASA), 2004)
This article gives a report on the author's attendance and experiences at the World Library Congress/IFLA Conference in Buenos Aires in 2004.
Keywords: IFLA; WLIC; Buenos Aires